PERAN LEMBAGA MEDIASI DALAM PENYELESAIAN SENGKETA BISNIS SYARIAH - Rudi Hermawan (Et-Tijarie, 2018)
ABSTRACTIn carrying out their duties, sometimes there are some irregularities that result in disputes between the Bank and the Customer. In Islamic banking, where there are disputes between customers and banks that are caused notfulfillment of the customer's financial demands by the bank, then in stagessettlement of customer complaints, the settlement can be soughtthrough banking mediation.Mediation is the process of resolving disputes through the processnegotiations or consensus of the parties assisted by the mediator. The main characteristic of the mediation process is the negotiationthe essence is the same as the process of deliberation or consensus.Mediation is the first step to resolve banking disputes by peaceful means outside the authority of the court. Keyword: Banking Mediation, Banking Mediation, Islamic Banking, Role ABSTRAKDalam melaksanakan tugasnya, terkadang ditemukan beberapa kejanggalan yg mengakibatkan terjadinya persengketaan antara Bank dan Nasabah. Dalam perbankan syariah, manakalah terdapat sengketa antara nasabah dengan bank yang disebabkan tidak terpenuhinya tuntutan finansial nasabah oleh bank, maka dalam tahap penyelesaian pengaduan nasabah, dapat diupayakan penyelesaiannya melalui mediasi perbankan. Mediasi merupakan proses penyelesaian sengketa melalui prosesperundingan atau mufakat para pihak dengan dibantu oleh mediator. Ciri utama proses mediasi adalah perundingan yangesensinya sama dengan proses musyawarah atau konsensus.Mediasi merupakan langkah awal untuk menyelesaikan persengkataan perbankan dengan jalan damai di luar kewenangan pengadilan. Kata Kunci: Lembaga Mediasi, Nasabah, perbankan, Peran